2022
DOI: 10.1093/cei/uxac054
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism on Prevotella melaninogenica promoting the inflammatory progression of oral lichen planus

Abstract: Oral lichen planus (OLP) is a common chronic inflammatory disease occurring in the oral mucosa. Bacteria is a key driver of mucosal immune response and can induce changes in gene expression and function of epithelial keratinocytes. IL-36γ can induce the expression of antimicrobial peptides, cytokines and chemokines, and is widely involved in many chronic inflammatory diseases. Our aim is to explore the role of IL-36γ in pathological process of OLP when Prevotella melaninogenica (P. melaninogenica) invades oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…cans fungi [48], but may also promote gingivitis, periodontitis, and lichen planus [47,[49][50][51][52]. We found that the mCherry Il1rl2 reporter was highly expressed in epithelial cells on the dorsal surface of the tongue (Figure 7A, black arrow).…”
Section: Vagina and Uterusmentioning
confidence: 84%
See 1 more Smart Citation
“…cans fungi [48], but may also promote gingivitis, periodontitis, and lichen planus [47,[49][50][51][52]. We found that the mCherry Il1rl2 reporter was highly expressed in epithelial cells on the dorsal surface of the tongue (Figure 7A, black arrow).…”
Section: Vagina and Uterusmentioning
confidence: 84%
“…The IL-36 system has been shown to activate expression of proinflammatory cytokines in oral epithelial cells [44,45]. This activity may be beneficial for the control of bacteria, e.g., Porphyromonas gingivalis and Prevotella melaninogenica [46,47], and Candida albicans fungi [48], but may also promote gingivitis, periodontitis, and lichen planus [47,[49][50][51][52]. We found that the mCherry Il1rl2 reporter was highly expressed in epithelial cells on the dorsal surface of the tongue (Figure 7A, black arrow).…”
Section: Oral Mucosa and Tonguementioning
confidence: 99%
“…Such various effects of individual species could be explained by large variability in their genomes. 42 The species, P. intermedia, P. nigrescense, and P. melanigencia have been consistently associated with infection, [43][44][45] inflammation, [46][47][48][49] and have also been linked to AD and associated mortality. 50 Conversely, it has been shown that P. buccae and P. corporis, two strains of Prevotella that exhibited strong suppression of protein aggregation and the associated toxicity, were found not to induce inflammation.…”
Section: Proteotoxic Bacteria Enhance the Aggregation And Toxicity Of...mentioning
confidence: 99%
“…Recent research has shown that PRP, either alone or in conjunction with other treatments, has the power to change the level of IL-6 in the saliva of OLP patients (12). Salivary level of IL-6 maybe used as a reliable marker for evaluating the therapeutic effectiveness of medications in OLP patients (13). Peripheral blood mononuclear cells and tissueinfiltrating mononuclear cells from OLP lesions both have the capacity to make tumour necrosis factor-alpha (TNF-α).…”
Section: Introductionmentioning
confidence: 99%